A leitura de imagem: Fayga Ostrower e Alberto Manguel, educadores do olhar - Pereira, Valeria Azambuja (2009)
This dissertation is about image reading under the perspective of the sight educators of Fayga Ostrower and Alberto Manguel. The approach of the theme starts by situating the ways that image reading has followed during these years in the theoretical proposals for the teaching of art. Since the Triangular Proposal of Ana Mae Barbosa and the concepts of reading and re-reading presented by Analice Dutra Pillar, the processes of image reading for children and teenagers through the research done Maria Helena Vagner Rossi and the methods of image reading organized by Edmund Feldmann and Robert Ott. I will present a biografical synthesis of the authors and the processes wich Fayga Ostrower and Alberto Manguel use to read images. Nevertheless, this dissertation mainly presents relations between the reading processes realized by Fayga Ostrower and Alberto Manguel and how these processes are fundamental in image reading.